Innovative Strategies for Safe E-Commerce Activities in Higher Education - Vaze, Vinod Moreshwar (SFIMAR Research Review, 2012)
Innovative Strategies and System for effective higher Education: The common tendency for effective higher education is more dependency on the latest Information Technology techniques. Photographic Memory Method, Video conferencing are just to name a few. Yes. With all the goodies of Information technology there are caveats too. The words "Hacker&Cracker" have become very tempting for the teenagers. They get excited and without complete knowledge they try to perform some deeds, just "for the heck of it", which they shouldn't have done and end up in trouble. Before any student tries to play "smart" and hack into some ones e-mail account, or try to misuse some ones credit/debit/ATM card he or she should be aware of the consequences and that exactly is what Cyber Law is all about. It is a myth that your IP (Internet Protocol) address cannot be traced. It is also a Myth that one would go scot-free. One can be traced even in remote area. There are varieties of Cyber Crimes: from Simple jovial acts, DDos, Virus/Worms attacks. Email frauds, cyber defacement. Data Didling, Trojans and Key-loggers to Cyber terrorism. Cyber Law is the law governing cyber space including higher education. Cyber law encompasses laws relating to: Cyber crimes. Electronic and Digital Signatures, Intellectual property. Cyber Forensic, data protections and privacy, integrity, authentication, non-repudiation and replay attacks. Digital evidence. Jurisprudence of Indian Cyber Law, instigation. Digital Signature certificates are a few of the tools used in a cyber Law. The bottom line: For effective Higher Education one needs to embrace Information Technology vis-avis Security. One also needs to make the transfer of data, essential for education SAFE. Thus one of the Innovative Strategies is to make Internet surfing safe for you and for me and for the entire universe. Ail E-commerce transactions have one thing in common. They are all convenient to use. One can perform the transactions sitting at home. They are also fast and efficient. They are paper-free. Yes they are. However, there is another side of the coin too. If not used properly they can prove hazardous. One has danger of losing all his life-time earnings in a few seconds! The common man wants to use all the latest facilities, and why not? But is he aware of the caveat the process carries? Unfortunately he is not aware. We need to make him alert and aware of all the tools and precautions one has to take before he starts using these facilities.